Mediating mechanism of posttraumatic growth as buffers of burnout and PTSD among nurses during the COVID-19 pandemic - Sim, Jae-Chang; Cha, Sun-Kyung; Im, Sun-Young (Frontiers in Public Health, 2024)
Objective The study aims to investigate factors that prevent burnout (BO) and symptoms of posttraumatic stress disorder (PTSD) while facilitating posttraumatic growth (PTG) among nurses combating the coronavirus disease 2019 (COVID-19) pandemic, with the purpose of validating the mediating effects of PTG. Methods A total of 247 nurses who provided patient care during the COVID-19 pandemic were enrolled, and a questionnaire was used to measure BO, PTSD, and PTG, data on deliberate rumination, emotional expression, adaptive cognitive emotion regulation (CER), maladaptive CER, and social support. The mediation path models for the effects of the predictors on BO and PS through the mediation of PTG were analyzed using the R Lavaan package. Results The results showed that deliberate rumination, emotional expression, and adaptive CER significantly increased PTG, while PTG significantly reduced BO and PTSD symptoms (PSs). However, maladaptive CER did not have a significant effect on PTG and only had significant direct effects on BO and PS. Bootstrapping confirmed that PTG significantly mediated the effects of all predictors. It partially mediated the effects of deliberate rumination and adaptive CER and completely mediated the effects of emotional expression. Conclusion Based on the results, it has been supported that deliberate rumination, emotional expression, and adaptive CER should be addressed as important variables in psychological interventions addressing nurses’ adversities during the pandemic. These variables can prevent BO and PS by facilitating PTG.